From waste to protein: a new strategy of converting composted distilled grain wastes into animal feed - Yu, Lei; An, Zichao; Xie, Dengdeng; Yin, Diao; Xie, Guopai; Gao, Xuezhi; Xiao, Yazhong; Liu, Juanjuan; Fang, Zemin (Frontiers in Microbiology, 2024)
Distilled grain waste (DGW) is rich in nutrients and can be a potential resource as animal feed. However, DGW contains as much as 14% lignin, dramatically reducing the feeding value. White-rot fungi such as Pleurotus ostreatus could preferentially degrade lignin with high efficiency. However, lignin derivatives generated during alcohol distillation inhibit P. ostreatus growth. Thus, finding a new strategy to adjust the DGW properties to facilitate P. ostreatus growth is critical for animal feed preparation and DGW recycling. In this study, three dominant indigenous bacteria, including Sphingobacterium thermophilum X1, Pseudoxanthomonas byssovorax X3, and Bacillus velezensis 15F were chosen to generate single and compound microbial inoculums for DGW composting to prepare substrates for P. ostreatus growth. Compared with non-inoculated control or single microbial inoculation, all composite inoculations, especially the three-microbial compound, led to faster organic metabolism, shorter composting process, and improved physicochemical properties of DGW. P. ostreatus growth assays showed the fastest mycelial colonization (20.43 μg• g -1 ergosterol) and extension (9 mm/d), the highest ligninolytic enzyme activities (Lac, 152.68 U• g -1 ; Lip, 15.56 U• g -1 ; MnP, 0.34 U• g -1 ; Xylanase, 10.98 U• g -1 ; FPase, 0.71 U• g -1 ), and the highest lignin degradation ratio (30.77%) in the DGW sample after 12 h of composting with the three-microbial compound inoculation when compared to other groups. This sample was relatively abundant in bacteria playing critical roles in amino acid, carbohydrate, energy metabolism, and xenobiotic biodegradation, as suggested by metagenomic analysis. The feed value analysis revealed that P. ostreatus mycelia full colonization in composted DGW led to high fiber content retention and decreased lignin content (final ratio of 5% lignin) but elevated protein concentrations (about 130 g• kg -1 DM). An additional daily weight gain of 0.4 kg/d was shown in cattle feeding experiments by replacing 60% of regular feed with it. These findings demonstrate that compound inoculant consisting of three indigenous microorganisms is efficient to compost DGW and facilitate P. ostreatus growth. P. ostreatus decreased the lignin content of composted DGW during its mycelial growth, improving the quality of DGW for feeding cattle.